2022
DOI: 10.3390/ijerph192113769
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Patterns of Cannabis- and Substance- Related Congenital Uronephrological Anomalies in Europe: Geospatiotemporal and Causal Inferential Study

Abstract: Introduction. Recent reports linking prenatal and community cannabis exposure to elevated uronephrological congenital anomaly (UCA) rates (UCAR’s) raise the question of its European epidemiology given recent increases in community cannabinoid penetration there. Methods. UCAR data from Eurocat. Drug use data from European Monitoring Centre for Drugs and Drug Addiction. Income from World bank. Results. UCAR increased across Spain, Netherlands, Poland and France. UCAR’s and cannabis resin THC increased simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 98 publications
2
8
0
Order By: Relevance
“…Interestingly, a companion paper to the present paper was recently published and showed that VACTERL syndrome (vertebral, anorectal, cardiac, tracheo-esophageal fistulae/esophageal atresia, renal and limb anomalies) was strongly and causally linked with European cannabinoid exposure [57,92]. In that esophageal atresia is part of the VACTERL syndrome this finding provides evidence from this other reference, confirming the present findings reported herein.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, a companion paper to the present paper was recently published and showed that VACTERL syndrome (vertebral, anorectal, cardiac, tracheo-esophageal fistulae/esophageal atresia, renal and limb anomalies) was strongly and causally linked with European cannabinoid exposure [57,92]. In that esophageal atresia is part of the VACTERL syndrome this finding provides evidence from this other reference, confirming the present findings reported herein.…”
Section: Resultssupporting
confidence: 91%
“…Many papers demonstrate that the dose-response relationship of cannabinoids with both genomic mutagenicity and mitochondrial toxicity is strongly exponential [52][53][54][55][56]. Moreover, this exponentiation of the dose-response effect has been extended to epidemiological studies where it has been repeatedly demonstrated that the passage from the fourth to fifth quintile of cannabinoid exposure is accompanied by a discontinuous quantum jump in congenital anomaly rates [5,[57][58][59][60].…”
Section: Introductionmentioning
confidence: 98%
“…There are various strengths and limitations to the present conceptualization. The strengths include the remarkable consistency across the many epidemiological studies, which clearly demonstrates the genotoxic harms of cannabis exposure in several different international jurisdictions, in relation to both the congenital anomalies [ 28 , 36 , 37 , 40 , 45 , 46 , 49 , 51 , 71 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ] and cancer [ 22 , 23 , 24 , 25 , 26 , 30 , 41 , 232 ], and, indeed, now also in aging [ 53 , 54 ]. Similar results in many different studies are clearly mutually supportive and strengthen the overall quality of the body of evidence.…”
Section: Mechanisms Of Cannabinoid Genotoxicitymentioning
confidence: 98%
“…For the reader who is unfamiliar with this epidemiological literature, it should be pointed out that most of the modern epidemiological studies referred to are not just observational ecological studies of convenience which happen to show a particular association. Many of the best studies used a formal space–time analysis and the quantitative tools of causal inference to introduce a pseudo-randomized quasi-experimental paradigm from which it is entirely appropriate to invoke causal associations [ 28 , 36 , 37 , 40 , 45 , 51 , 71 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore highly relevant that tripling levels of community cannabis exposure have been linked with a tripling of total birth defect rates in Canada’s northern provinces, and increased levels of cannabis exposure have been linked with higher rates of dozens of congenital anomalies in Hawaii, Colorado, Australia and the USA [ 44 , 45 , 46 , 47 , 48 , 49 ], affecting most major organ systems (cardiovascular, gastrointestinal, genitourinary, respiratory, neurological and body wall), including limbs and chromosomal anomalies, trisomies and monosomy [ 44 , 45 , 46 , 47 , 48 , 49 ]. Much data have come to light recently as a result of large studies of national and transnational datasets on this subject [ 44 , 46 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%